Recent advances in nanoparticle carriers for coordination complexes - Sato, Mariana Rillo [UNESP]; Silva, Patricia Bento da [UNESP]; Souza, Rodrigo Alves de [UNESP]; Santos, Karen Cristina dos [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publ Ltd, 2015)
Coordination compounds are substances in which a central metal atom is bonded to nonmetal atoms, or groups of atoms, called ligands. Examples include vitamin B-12, hemoglobin, chlorophyll, dyes and pigments, as well as catalysts used in organic synthesis. Coordination compounds have received much attention in recent years. This interest was prompted by the discovery that several coordination compounds exhibit activity against bacteria, fungi and cancer. Some coordination compounds are not in clinical use, because of poor water solubility. Because they are unable to cross the lipid membranes of cells, bioavailability and efficacy are low. Some researchers have applied nanotechnology to coordination compounds, hoping to reduce the number of doses required and the severity of side effects, and also to improve biological activity. Nanotechnology can deliver active components in sufficient concentrations throughout treatment, guiding it to the desired location of action; conventional treatments do not meet these requirements. In this study we review some drug delivery systems based on nanotechnology, such as microemulsions (MEs), cyclodextrin (CD), polymeric nanoparticles (PN), solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), magnetic and gold nanoparticles (MNPs / AuNPs) and liquid crystalline systems (LC), and coordination compounds.
Keywords: Biological activity; Coordination compound; Drug delivery systems; Metallic complex; Nanosystems; Nanotechnology